Efficacy of Abatacept Therapy in a Patient with Juvenile Idiopathic Arthritis and Bilateral Uveitis - Lelia A. Galstian; Elena S. Zholobova; Alexandra V. Starikova; Ekaterina V. Denisova (Вопросы современной педиатрии)
The article presents clinical observation of the patient at the age of 7 years suffering from severe juvenile idiopathic arthritis with uveitis refractory to standard antirheumatic therapy. The case complexity was determined by multiple joint damages, presence of bilateral uveitis, and hyperimmunoglobulinemia at the disease onset. The successful use of abatacept is described: remission from both the articular syndrome and uveitis, a 100% improvement by ACRpedi criteria are reached. The selection of a biological preparation was determined by a polyarticular joint disease, by the presence of active recurrent uveitis, as well as by immune status compromise for TB infection. A gradual increase in abatacept efficacy and remission maintenance for a long time period are demonstrated.